Regional Financial Ratio Analysis in Pemalang Regency For the 2016-2020 Financial Year - Dana Yuliana; Susanti Usman (Green Publisher Indonesia, 2022)
This study aims to determine regional financial performance based on the ratio of fiscal decentralization, regional financial independence ratio, effectiveness ratio, regional financial efficiency ratio, compatibility ratio, and growth ratio in Pemalang Regency for the 2016-2020 fiscal year. The method in this research is descriptive quantitative. The data used in the form of secondary data in the form of an annual report on budget realization from the official website of the Pemalang Regency government. The results of this study are the ratio of the degree of fiscal decentralization is included in the very good category, the independence ratio is included in the delegative category, the effectiveness ratio is included in the effective category, the efficiency ratio is included in the efficiency category, the compatibility ratio of the results of the realization is more optimized for routine capital expenditure purposes, and The result of the percentage growth ratio of the Pemalang Regency government prioritizes its regional expenditures for operating expenses compared to its capital expenditures. The performance of local financial management in Pemalang Regency based on financial ratio analysis is quite good, in managing PAD it is effective and efficient, and the level of regional independence is good.